L-Fucose-containing arabinogalactan-protein in radish leaves. (13th October 2015) - Inaba, Miho; Maruyama, Takuma; Yoshimi, Yoshihisa; Kotake, Toshihisa; Matsuoka, Koji; Koyama, Tetsuo; Tryfona, Theodora; Dupree, Paul; Tsumuraya, Yoichi
Highlights: A radish leaf arabinogalactan-protein (AGP) that containsl -fucose (l -Fuc) residues. Structure of the AGP was analyzed by digestion with exo-β-(1→3)-galactanase. l -Fuc found attached to both uronic acids andl -arabinose through α-(1→2)-linkages. Neutral and acidicl -Fuc-containing oligosaccharides from the AGP were isolated. Graphical abstract: Abstract: The carbohydrate moieties of arabinogalactan-proteins (AGPs) have β-(1→3)-galactan backbones to which side chains of (1→6)-linked β-Gal residues are attached through O -6. Some of these side chains are further substituted with other sugars. We investigated the structure ofl -Fuc-containing oligosaccharides released from the carbohydrate moieties of a radish leaf AGP by digestion with α-l -arabinofuranosidase, followed by exo-β-(1→3)-galactanase. We detected a series of neutral β-(1→6)-galactooligosaccharides branching variously at O -3 of the Gal residues, together with corresponding acidic derivatives terminating in 4- O -methyl-GlcA (4-Me-GlcA) or GlcA at the non-reducing terminals. In neutral oligosaccharides with degree of polymerization (dp) mainly higher than 10, l -Fuc groups were attached throughl -Ara residues as the sequence, α-l -Fuc p -(1→2)-α-l -Ara f -(1→. This sequence was verified by isolation of the pentasaccharide α-l -Fuc-(1→2)-α-l -Ara f -(1→3)-β-Gal-(1→6)-β-Gal-(1→6)-Gal upon digestion of the higher oligosaccharides with endo-β-(1→6)-galactanase. By contrast, in lower polymerized (predominantly dp 4) acidic oligosaccharides, l -Fuc groups were attached directly at the non-reducing terminals through α-(1→2)-linkages, resulting in the release of the tetrasaccharides, α-l -Fuc p -(1→2)-β-GlcA-(1→6)-β-Gal-(1→6)-Gal and α-l -Fuc p -(1→2)-β-4-Me-GlcA-(1→6)-β-Gal-(1→6)-Gal. In long acidic oligosaccharides with dp mainly higher than 13, l -Fuc groups localized on branches were attached to the uronic acids directly and/orl -Ara residues as in the neutral oligosaccharides.